PP.83 Can We Predict Poor Pregnancy Outcomes in Women Presenting with Reduced Fetal Movements?. (26th April 2013) - Skorupskaite, K; Love, C
Abstract : Objectives: Reduced fetal movements (RFM) are associated with adverse pregnancy outcomes, including intrauterine growth restriction (IUGR) and stillbirth. The aim was to review risk factors which could predict poor perinatal outcomes in women presenting with RFM. Methods: A retrospective patient record review was performed of women presenting to a Scottish tertiary centre with RFM during November 2011. Results: 118 women were assessed for RFM. The study population had the majority of risk factors known to be associated with IUGR/stillbirth. Women with RFM and risk factors for IUGR/stillbirth had statistically significant more pre-term deliveries and more babies born with low birth weight compared to women with no risk factors (Table 1 ). Although women with recurrence of RFM had more pre-term and stillbirth deliveries and babies with low birth weight compared to women presenting once with RFM, the results failed to show statistical significance. There was no difference in pregnancy outcomes between women with reassuring CTG and ongoing perception of RFM compared with those women with reassuring CTG and perceived fetal activity during the assessment (Table 1 ). Conclusion: Risk factors for IUGR/stillbirth are significant determinants of poor pregnancy outcomes in women presenting with RFM.